2010
DOI: 10.1080/09670260903518439
|View full text |Cite
|
Sign up to set email alerts
|

An improved coverslip method for investigating epipelic diatoms

Abstract: The traditional coverslip method for harvesting motile diatoms was improved and standardized by determining optimum times for diatom harvesting; by using opaque Petri dish bases as experimental chambers; and by preparing coverslips by burning. Three experiments were conducted to evaluate the harvesting efficiency of the coverslip method. Experiment 1 was performed to reveal the spatial distribution of epipelic diatoms on the coverslips after exposure periods ranging from 2 to 36 h. The transect count results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Diatom abundances were expressed quantitatively using a modified coverslip method (Yang et al. 2010) so that the motile epipelic diatoms could be discriminated from the total diatom abundances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diatom abundances were expressed quantitatively using a modified coverslip method (Yang et al. 2010) so that the motile epipelic diatoms could be discriminated from the total diatom abundances.…”
Section: Discussionmentioning
confidence: 99%
“…Wetted lens tissue squares (2 · 2 cm) were placed on each tube and orientated towards the light source to encourage motile diatoms to migrate out of the substrate biofilm. After Yang et al (2010), the lens tissue squares were exposed for 8 h (8 a.m.-4 p.m.) before careful removal. The sample lens tissues were then extracted for Chl a using degassed acetone overnight at 4°C (USEPA 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bicarbonate anions are used by algae as a carbon source for photosynthesis, thus its availability greatly affects aquatic algae existence. Yang et al (2010) demonstrated that CO 2 concentration affects the existence of epipelic diatoms in aquatic environments. A sufficient quantity of dissolved organic material is needed by the algae.…”
Section: Correlation Between Epipelic Diatoms and The Quality Of Watementioning
confidence: 99%